Does Timing of Diagnosis of Hypertensive Disorders of Pregnancy Impact Blood Pressure Resolution? - Broni, Eric K.; Perdigao, Joana Lopes; Koelper, Nathanael; Lewey, Jennifer; Levine, Lisa D. (American Journal of Perinatology, 2024)
Hypertensive disorders of pregnancy (HDP) can be diagnosed prior to labor, during labor, or postpartum. We evaluated whether the timing of HDP diagnosis impacts postpartum blood pressure (BP) outcomes.Secondary analysis of 384 patients with HDP from a trial evaluating furosemide use on BP outcomes. The timing of HDP diagnosis was categorized into diagnosis in the antepartum period, prior to labor versus diagnosis peripartum (during labor or first day of postpartum). Outcomes included time to resolution of hypertension and persistent hypertension 7 days' postpartum. Logistic and Cox regression models were used.Patients diagnosed in the peripartum period had a shorter median time to postpartum BP resolution after adjusting for severity of HDP, mode of delivery, and furosemide use (5.5 vs. 6.5 days, adjusted hazard ratio: 1.18, 95% confidence interval [1.11–1.25]).Patients diagnosed with HDP in the peripartum period experience a faster BP resolution than those diagnosed in the antepartum period.
Keywords: hypertensive disorders of pregnancy; peripartum hypertension; postpartum hypertension; labor; timing of HDP diagnosis